Pivotal Role of Mediterranean Dietary Regimen in the Increase of Serum Magnesium Concentration in Patients with Coronary Artery Disease - Nimah Bahreini; Mojgan Gharipour; Hossein Khosravi-Boroujeni; Hojjat Rouhi-Boroujeni; Afshin Shiranian; Amin Salehi-Abargouei; GholamReza Sharifzadeh (Journal of Nutrition and Metabolism)
Background. Recent studies confirmed cardioprotective role of intravenous magnesium for the prevention of cardiac events, but effect of dietary intake of this mineral via recommended dietary regimens on control and inhibition of coronary artery disease (CAD) risk factors has been questioned. The aim of the present study was to determine effect of Mediterranean dietary approach on serum magnesium concentration among Iranian patients with CAD. Method. Baseline characteristics and clinical data of 102 consecutive patients with the diagnosis of CAD and candidates for isolated coronary artery bypass surgery were entered into the study. Laboratory parameters especially serum magnesium concentration were measured after 12–14 h of overnight fasting and before operation. Nutritional status was assessed by food frequency questionnaire and the diet score was calculated on the basis of Mediterranean diet quality index (Med-DQI). Results. No significant differences were found in the concentrations of albumin, last fasting blood sugar, last creatinine, and lipid profiles between the groups with Mediterranean dietary score < 5 and the group with higher dietary score; however, serum magnesium concentration in the first group was higher than that in the group with higher dietary score. Linear multivariate regression analysis showed that the lower Mediterranean dietary score was a predictor for serum magnesium concentration after adjusting for confounders. Conclusion. Taking Mediterranean dietary regimen can be associated with increased level of serum magnesium concentration, and thus this regimen can be cardioprotective because of its effects on serum magnesium.